Inhibition of Germination and Seedling Development of Atriplex Canescens - Al-Charchafchi, F M.R; Clor, M A (Annals of Arid Zone, 2016)
Germination of A/rip/ex canescens seeds without bracts was reduced fromÂ 100% to about 80-85% when removed bracts were placed in vicinity.Seeding growth was arrested and the root tips of very young seedlingsÂ dJmaged in the presence of dry bracts. Water extract of the bracts hadÂ similar effects.